The preparation, delivery and outcome of COVID-19 pandemic training program among the Emergency Healthcare Frontliners (EHFs): the Malaysian teaching hospital experience - Mohd Hisham I,; Azlan Helmy Abd Samat,; Ismail Mohd Saiboon, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
One of the strategies in strengthening the healthcare providers in mitigating the impact of COVID-19 pandemic is through training. Safety and disease unfamiliarity with COVID-19 was the main reason for developing this dedicated specialized training modules in order to address the issue. The training modules were developed based on three strategies that are learning from experience, design suitable dedicated module and identify weakness and vulnerability. The training modules created were donning-doffing of Personal Protective Equipment (PPE), airway management and cardiopulmonary resuscitation of suspected COVID-19 patients which were delivered through immersive life simulation technique. A total of 178 Emergency Healthcare Frontliners (EHFs) were trained. Each module was guided with a checklist that the participants found to be very useful. None of the participants reported developing symptoms of infection after undergoing the face-to-face simulation training even after two weeks of post-training periods. Seven important steps were found to be crucial that contributed to these findings which included room space, participants number per group, COVID-19 screening, taking of temperature, hand sanitization, PPE, and equipment sanitization before and after training. Hands-on training with guided-checklist was found to be very useful to the EHFs in managing an unfamiliar situation of COVID-19. In time-constraint-resource-limited conditions, training modules should be focused on addressing the pressing problem at hand. In conducting a face-to-face training, precautionary safety measures should be strictly adhered to prevent the spread of the disease.